2020
DOI: 10.3390/nano10081466
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Shear Bond Strength and Antibacterial Activity of Orthodontic Adhesive Containing Silver Nanoparticle, an In-Vitro Study

Abstract: This study evaluated the effect of incorporating silver nanoparticles (AgNPs) into conventional orthodontic adhesive on its antibacterial activity and the shear bond strength (SBS) to stainless steel orthodontic brackets. Thirty-four extracted premolars were randomly allocated into two groups (n = 17). Orthodontic adhesive (Transbond XT, 3M Unitek) was blended with AgNPs (50 nm, 0.3% w/w) to form a nano-adhesive. In order to bond stainless steel twin brackets (0.022-inch, American Orthodontics), Transbond XT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 34 publications
5
51
0
1
Order By: Relevance
“…The use of nanoparticles as reinforcing filler improves the mechanical, physical, and working properties of dental composites, as opposed to macro or micro-sized fillers [ 34 ]. The researchers have incorporated various therapeutic ions including silver nanoparticles (AgNPs) [ 35 ], zirconium oxide–titanium dioxide (ZrO 2 -TiO 2 ) nanoparticles [ 36 ], copper-doped bioactive glass nanoparticles (CuBGn) [ 37 ], and n-HA to improve the properties of adhesives [ 38 ]. The n-HA offers superior biocompatibility to act as a source of calcium and phosphate, in addition to possessing a strong ability to bond with tooth proteins [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of nanoparticles as reinforcing filler improves the mechanical, physical, and working properties of dental composites, as opposed to macro or micro-sized fillers [ 34 ]. The researchers have incorporated various therapeutic ions including silver nanoparticles (AgNPs) [ 35 ], zirconium oxide–titanium dioxide (ZrO 2 -TiO 2 ) nanoparticles [ 36 ], copper-doped bioactive glass nanoparticles (CuBGn) [ 37 ], and n-HA to improve the properties of adhesives [ 38 ]. The n-HA offers superior biocompatibility to act as a source of calcium and phosphate, in addition to possessing a strong ability to bond with tooth proteins [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Eslamian et al . ( 17 ) demonstrated that the incorporation of AgNPs with a particle size of 50 nm at a concentration of 0.3% into an orthodontic resin had an important activity against S. mutans , this antibacterial property was sTable for 30 days of evaluation. Yassaei et al .…”
Section: Discussionmentioning
confidence: 99%
“…Silver-nanoparticles (AgNPs) have been used due to their antibacterial properties and low toxicity to human cells. Previous studies have shown that incorporating AgNPs to orthodontic resins has an important antibacterial effect, inhibiting the growth of S. mutans in in vitro models ( 11 , 12 , 17 ). However, to our knowledge its preventive effect on the formation of WSLs has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These fibers when combined with RMGIC showed a considerable improvement in the flexure strength and fracture toughness. Short glass fibers increased the flexural strength by 50 % whereas long braided fibers significantly enhanced the fracture toughness 69.…”
Section: Modified and Anticariogenic Rmgicmentioning
confidence: 95%